Rosuvastatin exposure in female Wistar rats alters uterine contractility and do not show evident (anti)estrogenic effects - de Barros, Jorge Willian Franco [UNESP]; Villela e Silva, Patrícia [UNESP]; Silva, Gustavo Venâncio da [UNESP]; da Silva, Katiussia Pinho [UNESP]; Borges, Cibele dos Santos [UNESP]; Mueller, André [UNESP]; Valencise, Lethícia [UNESP]; Pupo, André Sampaio [UNESP]; Kempinas, Wilma De Grava [UNESP] (Taylor & Francis, 2021)
Statins are 3-hydroxy-3-methyl-glutaryl-CoA (HMG-CoA) reductase inhibitor drugs that lead to serum-cholesterol-lowering effects. Rosuvastatin, a third-generation statin, has shown better results in reducing cholesterol concentrations when compared to other widely prescribed statins. Recent studies by our group reported that rosuvastatin impairs reproductive function in rats possibly by disrupting the reproductive-endocrine axis. In this study, we evaluated whether rosuvastatin presents estrogenic or antiestrogenic effects, by an in vivo uterotrophic assay in rats, and investigated the direct effect of this drug upon rat uterine tissue contractility both in non-gravid and gravid periods. Rosuvastatin exposure in vivo at doses of 0 (control), 3, and 10 mg/kg/d was not associated with estrogenic or antiestrogenic effects on uterine tissue. However, in vivo (doses of 0, 3, and 10 mg/kg/d) and ex vivo (concentrations of 0, 1, 10, and 100 µg/mL) exposures to this drug were related to alterations in uterine basal contraction pattern. Furthermore, in vivo and ex vivo rosuvastatin exposures potentially modulate the action of uterine contraction inducers carbachol, norepinephrine, and prostaglandin E2. Thus, rosuvastatin can affect uterine physiology not necessarily by an endocrine mechanism related to the estrogen signaling, but possibly by its pleiotropic effects, with indirect tissue and cellular interactions, since in vivo and ex vivo exposures of uterine fragments to rosuvastatin presented different responses in uterine contractile parameters, which require further studies upon the precise mechanism of action of this drug in female reproductive function.
Keywords: reproductive toxicology; Statin; uterine contractility; uterotrophic assay